Phenolic environmental estrogens in urine and blood plasma from women with uterine leiomyoma: Epidemiological survey. Issue 4 (3rd February 2016) - Shen, Yang; Dong, Yi‐Min; Lu, Qing; Xu, Jie; Wu, Yan‐Ting; Yun, Seong Seok; Ren, Mu‐Lan
Abstract: Aim: To explore the effect of phenolic environmental estrogens (EE) on women with uterine leiomyoma (UL). Methods: Urine and blood plasma samples were collected from 300 patients diagnosed with UL at the Affiliated Zhongda Hospital of Southeast University between December 2013 and December 2014. Control urine and blood plasma samples were collected from 300 women who are either patients without UL or healthy volunteers presenting to the same hospital for physical examination during the same period. Bisphenol A (BPA), nonylphenol (NP) and octylphenol (OP) concentration in these samples was measured using solid phase extraction (SPE) coupled with liquid chromatography–tandem mass spectrometry. Results: The OP concentration in urine and blood plasma was significantly higher in the UL group compared with the control group ( r = 0.224, P = 0.001). Urine BPA concentration was not significantly different between the UL group and the control group ( r = 0.009, P = 0.896). There was also no statistically significant difference in urine NP concentration between the two groups ( r = 0.057, P = 0.419). On logistic regression, exposure concentration of urine BPA (OR, 1.129; 95%CI: 1.081–1.179) and NP (OR, 1.165; 95%CI: 1.025–1.324) was associated with UL genesis ( P < 0.05). Nevertheless, there was no significant difference in blood plasma concentration of BPA, OP and NP between the two groups ( P > 0.05). Conclusion: Urine and blood plasma EE exposure levels in women, especially the urine level, was related to the incidence of UL.